Microenvironmental stimuli for proliferation of functional islet β-cells - Alismail, Hanan (BioMed Central, 2014)
Diabetes is characterized by high blood glucose level due to either autoimmune destruction of islet β-cells or insufficient insulin secretion or glucose non-responsive production of insulin by β-cells. It is highly desired to replace biological functional β-cells for the treatment of diabetes. Unfortunately, β-cells proliferate with an extremely low rate. This cellular property hinders cell-based therapy for clinical application. Many attempts have been made to develop techniques that allow production of large quantities of clinically relevant islet β-cells in vitro. A line of studies evidently demonstrate that β-cells can proliferate under certain circumstances, giving the hopes for generating and expanding these cells in vitro and transplanting them to the recipient. In this review, we discuss the requirements of microenvironmental stimuli that stimulate β-cell proliferation in cell cultures. We highlight advanced approaches for augmentation of β-cell expansion that have recently emerged in this field. Furthermore, knowing the signaling pathways and molecular mechanisms would enable manipulating cell proliferation and optimizing its insulin secretory function. Thus, signaling pathways involved in the enhancement of cell proliferation are discussed as well.